Can Religious Belief Be a Pathological Defence?: A Modified Systematic Literature Review Concerning an Issue Related to the Psychotherapeutic Relationship Interspersed With Case Illustrations From Clinical Practice - Morris, Julian (Auckland University of Technology, 2006)
This dissertation is concerned with how psychotherapists appraise the health of their clients’ religious beliefs when pathology is suspected to be interwoven with client’s belief systems. While the study has a specific clinical focus it has wider implications concerning the confluence between psychotherapists and psychotherapy with religious clients (client’s who espouse religious beliefs) and religion within the therapeutic relationship. Freud’s dismissal of religion as exclusively a neurotic expression representing individuals’ need for Oedipal protection from existential anxiety is found to be an unsatisfactory explanation for the numerous psychological functions of religious beliefs in clients’ lives. This study is inclusive of the differing perspectives and forms, both healthy and pathological, regarding religious involvement. This study uses a modified systematic literature review to search primarily theoretical and clinical literature but also includes two empirical studies looking at the correlation between individuals’ religious investment and mental health. From a review of related material it is observed that there are significant deficiencies within the literature about clinical issues related to working with clients’ religious beliefs. It is argued that this gap in the literature may be representative of Freud’s legacy and felt to have contributed to an avoidant and uninformed ‘culture’ to be promoted within psychodynamic psychotherapy with respect to religion and the religious beliefs of clients. Conclusions are drawn with regard to the influence of this ‘culture’ on the ability for psychotherapist to work in an informed way with their religious clients. Due to the lack of guidance within the field, suggestions are made about the need for psychotherapists to become cognisant of specific therapeutic dynamics when working with clients’ religious beliefs. Future directions in research within this area are considered.
Keywords: Psychology and religion; Psychiatry and religion; Psychotherapy; Religious aspects